Organized Communities and Potable Water Public Utilities in Colombia: Advocacy for the Third Economic Option Based on the Common-pool Resources Theory (2013)
Based on the theory and institutional principles proposed by Elinor Ostrom, this paper explores whether Colombian organized communities are able to provide potable water public utility in a sustainable manner and manage it as a common-pool resource (CPR) -- For this purpose, a set of Colombian community aqueducts is selected and compared against the eight principles proposed by this theory -- The results have shown that, in general it complies with institutional principles but it also highlights difficulties, particularly in regards to the "minimal recognition of organization rights" principle